Religious Ethics and Moral Realism - Hajj Muhammad Legenhausen (اخلاق وحیانی, 2015)
The purpose of this paper is to explore the relations between various forms of moral realism and some views about religious ethics, particularly, religious ethics in the Islamic tradition, although much of what is said will apply to ethical views in other religious traditions, as well. First, there is a brief historical review of the rise of moral realism in the twentieth century. Second, the major types of moral realism are distinguished. Third, it is argued that for each of the major types of moral realism, from robust moral realism to minimalist moral realism, religious views of ethics can be formulated that are compatible with both realism and its denial. In each case, however, the religious ethicist must pay a price for taking on realism or its denial. Finally, it is argued that the position taken by major Muslim philosophers in the tradition of Ibn Sina through Mulla Sadra is one that concurs with the non-realist position on a number of significant points.